A Virtual Reality Game-Based Approach for Shoulder Rehabilitation - Moreira, Moisés (2024)
In recent years, with widespread access to virtual reality (VR) headsets, VR has become an affordable supplement to physiotherapy. Researchers explore the use of existing commercial games or develop new ones to enhance physiotherapy sessions, finding that gamers exhibit reduced nervousness, report less pain, and experience increased enjoyment. However, ensuring consistent exercise adherence poses a challenge. Another area of interest involves integrating robots to aid patients. In our study, we seamlessly integrated a Kuka LBR Med 7 R800 with Unity through a meticulously developed Application Programming Interface (API). This fusion of robotics and video games assists in physiotherapeutic exercises. The games were developed specifically for compatibility with the Oculus Quest 2 virtual reality headset, chosen as the preferred VR platform for this study. Two games, using common game-design concepts with distinct approaches, were evaluated for system acceptance via the Technology Acceptance Model (TAM) and usability through the System Usability Scale (SUS). In a well-distributed group of 15 participants with an average age of 22 years, greater technology acceptance was observed among women. Those playing more hours per day reported lower perceived ease of use, though one game achieved an excellent SUS rating of 83.3. Conversely, the other game, which was tested with 11 participants with an average age of 20 years, showed a potential negative impact on behavioral intention. The particular sample used in the study has limitations, so the study should be repeated to obtain more reliable and conclusive results. In conclusion, the successful integration of VR and robot assistance in physiotherapy games relies on the proper application of the game design principle.